Omaezallene from Red Alga Laurencia sp.: Structure Elucidation, Total Synthesis, and Antifouling Activity - Umezawa, Taiki; Oguri, Yuko; Matsuura, Hiroshi; Yamazaki, Shohei; Suzuki, Masahiro; Yoshimura, Erina; Furuta, Takeshi; Nogata, Yasuyuki; Serisawa, Yukihiko; Matsuyama-Serisawa, Kazuyo; Abe, Tsuyoshi; Matsuda, Fuyuhiko; et al. (Angewandte Chemie, 2014)
Natural antifouling products have been the subject of considerable attention. We screened marine algae for antifouling activity and discovered omaezallenes, the new bromoallene‐containing natural products isolated from the red alga Laurencia sp. Described is the isolation, structure elucidation, and total syntheses of omaezallenes. The relative and absolute configurations of natural omaezallenes were unambiguously established through total synthesis. The antifouling activities and ecotoxicity of omaezallenes were also evaluated. Ein neuer bromierter Naturstoff – das aus der Rotalge Laurencia sp. isolierte Omaezallen – wurde synthetisiert und einer NMR‐Strukturaufklärung unterzogen. Die Wirkung von Omaezallen und seinen Isomeren gegen Bewuchs durch Cyprislarven der Gestreiften Seepocke (Amphibalanus amphitrite) wurde untersucht.